RELEVANSI KONSEP PENDEKATAN HUMAN SECURITY MAHBUB UL HAQ DALAM PENCEGAHAN PERKEMBANGAN TERORISME INTERNASIONAL - , Sumarno ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human Security which was constructed by Mahbub ul Haq as the non traditional security approach would to maps the causes of every international and domestics issues as the threat to humanity, when and whereas, by implementation with sustainably development. International terrorism one of complexis phenomena and international security issues its growing can be restrained with Human Security approach like Mahbub ul Haq concept, because Human Security approach could to gasped and made maping the roots of terrorism causes who is source frome political, economic, culture, social, and religious aspects. The objective of research, first to know relevant concept about Human Security which was constructed by Mahbub ul Haq to prevent the growing of international terrorism. Second, to know the strength and weakness of Human Security as non traditional approach for restraining the growing of international terrorism. This research was designed with qualitative descriptive method non experimental. Research material is Human Security conception and literature which has discussed about international terrorism, and subject of research is Mahbub ul Haq who as the basic layer of Human Security. Data collecting was executed with library research and documentary study, validation data was executed with technique of triangulation. Data analysis has be executed with qualitative method, continually, repeatedly and sustainably. The result of research has shown that Human Security relevant to restrain the growing of international terrorism which was rooted in economic poverty factor and injustice of world economic order and irrelevant for prevent the growing of international terrorism who have oriented political interest. The strength of Human Security to restrain international terrorism was located in liberal insight which provided the basic for implementation and emphasize on cooperations and responsibility of global institution. Whereas, the weakness be located in presence conflict between global interest versus national interest in implementation of Human Security and inpreparation domestic system